Delay-dependent guaranteed-cost control based on combination of Smith predictor and equivalent-input-disturbance approach. (May 2016) - Gao, Fang; Wu, Min; She, Jinhua; He, Yong
Abstract: This paper presents a new system configuration and a design method to improve control performance for a system with an input time delay and disturbances. The equivalent-input-disturbance approach is extended to handle a time-delay system. It is combined with the Smith predictor to reject disturbances. A delay-dependent stability condition is devised in terms of a matrix inequality by using the free-weighting matrix approach. The gain of the observer is designed by applying the cone complementary linearization method to the matrix inequality. A numerical example demonstrates the validity of the method. Abstract : Highlights: Present a design method to improve control performance against disturbances. Equivalent-input-disturbance (EID) approach is extended to handle a time delay system. A delay-dependent stability condition is devised by the free-weighting matrix approach. The gain of the state observer is designed by the cone complementary linearization method. The SP-EID control method demonstrates its validity and the superiority.